Revitalizing 21st-Century Education Through Technology-Based Learning Management at SD Negeri 54 Banda Aceh - Akmaluddin, Akmaluddin; Sari, Siti Mayang (IJBLE Scientific Publications Community Inc., 2024)
This research aims to analyze and explain technology-based learning management at State Elementary School 54 Banda Aceh to support the revitalization of 21st century education. Revitalization of education is a necessity to accommodate the challenges that arise along with technological developments. Learning management plays an important role in creating changes that support the revitalization of education that is able to respond to the dynamics of current developments. This research was carried out at State Elementary School 54 Banda Aceh. This research use desciptive qualitative approach. The results of the research show that the Principal of State Elementary School 54 Banda Aceh has carried out good management and supervision regarding the challenges and benefits of implementing technology-based learning. This aims to support the revitalization of 21st century education with a focus on 21st century learning and technology that emphasizes students' 4C skills and the activities carried out need to be controlled according to plan so that learning objectives are achieved. Management of technology-based learning at State Elementary School 54 Banda Aceh includes planning, organizing, coordinating and supervising carried out by the school principal.